Effect of catalyst particle shape on heat and mass transfer in steam methane reforming - Igor Karpilov; Dmitry Pashchenko (Case Studies in Thermal Engineering)
Steam methane reforming (SMR) is a complex process with several intertwined dependencies. An important factor is heat transfer between the reaction mixture and the catalyst, which greatly affects CH4 conversion. The present manuscript investigates the influence of catalyst particle shape on heat transfer characteristics during SMR reactions. A numerical model based on the CFD approach was developed to compare different catalyst shapes and determine the optimal one. Five catalyst shapes: sphere, cylinder, Raschig ring, 7-hole cylinder, and trilobe were analyzed under varying operating conditions (inlet velocities of 0.25–1.5 m/s, temperatures of 700–1100 K, and particle diameters of 2.5–20 mm). The results demonstrate that Raschig rings and 7-hole cylinders exhibit the highest total heat flow, consuming up to 276 W under optimal conditions (T = 1100 K, v = 1.5 m/s), while spherical particles with a diameter of 20 mm achieve the highest heat flux (19320 W/m2) due to their streamlined geometry. In contrast, Raschig rings provide the highest mass-specific heat flow (3520 W/kg), outperforming 7-hole cylinders by 12.5% and trilobe particles by 15%. The study reveals that catalyst performance is governed by three key factors: high surface area, low flow resistance, and streamlined shape. These findings provide critical insights for optimizing catalyst design in industrial SMR applications, balancing reactor volume efficiency (favoring spheres) and economic feasibility (favoring Raschig rings).